Human Resource Quality in Managing the Village Information System: Kualitas Sumber Daya Manusia dalam Mengelola Sistem Informasi Desa - Pramesswary, Ikko Della; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to assess and analyze the quality of human resources among village officials in implementing the Village Information System (SID) program in Gemurung Village, Gedangan District, Sidoarjo Regency. Using a qualitative descriptive method, data were collected through interviews, observations, and documentation, and analyzed using the Miles & Huberman model. The findings reveal that while village officials understand SID functions, their knowledge remains suboptimal due to challenges in integrating SID with public services and less relevant educational backgrounds. Information technology mastery is low, primarily due to limited training opportunities. In terms of skills, innovation and creativity are still limited, as officials only utilize basic features of the free version. Nevertheless, SID supports fast, accurate, and efficient public services. Regarding data processing and software capabilities, village officials perform well, enabling accurate and relevant decision-making. Highlights: Limited IT Mastery: Village officials struggle with SID due to minimal training and low technological proficiency. Underutilized Features: Innovation is lacking as only basic SID features are used, limiting its full potential. Effective Data Use: Despite challenges, officials show strength in processing data for accurate decision-making. Keywords: Human Resources Quality, Village Government, Village Information System